Utilization of blockchain in the application of master data management - Martins, Daniel Filipe Catita (2016)
As the name implies, Master Data Management (MDM) manages Master Data: the set of core information needed and shared in the systems of an enterprise. Depending on the scope of the organization, master data could be data about clients if all the systems consider client information critical for their operations and decision making. A fundamental concept of MDM is the Golden Record, an entry with the best and more valuable information about an entity, formed through the application of rules and methods on the data that exists scattered over the systems. It is the single version of the truth. Master Data Management solutions are dependent of a centralized data hub that holds the most valuable information. The solution proposed disrupts the list of o ers, combining the Master Data Management concept with the Blockchain technology, resulting in an MDM solution with a distributed data hub that is truly decentralized. A Blockchain consists on a chain of blocks that requires computational work to attach new blocks to the end of the chain, and where blocks cannot be changed without redoing the computational e ort for all the following blocks, resulting on a trusted environment. Participants of the Blockchain network hold a full copy of the Blockchain, making it a distributed network of information. Its security protocols and requirements eliminate the need for an intermediary between transactions and make Blockchain ideal to save things of value. The solution involves Ethereum: a Blockchain platform where transactions have programmable functionality, known as Smart Contracts, pieces of code containing a set of data and executable functions that are available through the public address. As all the data inserted through the programmed Smart Contracts goes through the same speci c cleansing, matching and merging rules, all the network participants will be in possession of the same Golden Records, resulting in a single view of entity. To facilitate the utilization of the solution, a wrapper and user interface were developed, granting that the user does not need to interact directly with the Blockchain.